2006
DOI: 10.2175/106143006x111934
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Coliphage PRD1 in a Surface Flow Constructed Wetland

Abstract: A tracer study was conducted in a 3-ha surface flow constructed wetland to analyze transport performance of PRD1, an enteric virus model. The convection-dispersion equation (CDE), including a firstorder reaction model, adequately simulated transport performance of PRD1 in the wetland under an average hydraulic loading rate of 82 mm/d. Convective velocity (v) and longitudinal dispersion coefficient (D) were estimated by modeling a conservative tracer (bromide) pulse through the wetland. Both PRD1 and bromide we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, studies that examined the transport or removal of pathogenic viruses in wetlands (e.g. Neralla & Weaver, 2000;Vidales-Contreras et al, 2006) were included, as these may provide important information on the behaviour of naturally occurring viruses. A study on virus-like particles in wetlands (Stott & Tanner, 2005) was included for similar reasons.…”
Section: Methodsmentioning
confidence: 99%
“…However, studies that examined the transport or removal of pathogenic viruses in wetlands (e.g. Neralla & Weaver, 2000;Vidales-Contreras et al, 2006) were included, as these may provide important information on the behaviour of naturally occurring viruses. A study on virus-like particles in wetlands (Stott & Tanner, 2005) was included for similar reasons.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, Vidales-Contreras and colleagues have performed a number of tracer experiments with seeded PRD1 and bromine that largely corroborate the findings discussed above. They have shown that PRD1 persists for longer than MS2 in HSSF wetlands and is thus a more conservative indicator (Vidales et al, 2003), that overall reduction rates are greater than inactivation rates (decay rates of −1.17 −d vs. −0.16 −d , respectively) suggesting that physical removal via initial adsorption is a more important than virus inactivation in HSSF systems (Vidales et al, 2003), and that plant and media surface area are critical to efficient virus reduction, observing greater reduction of PRD1 in HSSF than FWS systems (Vidales-Contreras et al, 2006), reporting a PRD1 LR of Above we have shown that GW constructed wetlands as a single unit process cannot reliably meet all reuse criteria; however, neither can traditional wastewater treatment unit processes, as evidenced by the need for final polishing or disinfection unit processes at wastewater treatment plants. Constructed wetlands can however generally provide 1-2 LR for most pathogen indicators and species including conservative viral indicators, particularly if media contact time is emphasized.…”
Section: The Ranges Inmentioning
confidence: 99%
“…These rates represent net losses of P22 in the water column and are similar to the rates reported in the literature for surface waters. For example, a value of 0.3 per day was reported in ref for bacteriophage PRD1 in a constructed wetland with significant surface flow. We notice that similar values of k I were obtained for both reaches, suggesting comparable solar inactivation effects in the two reaches.…”
Section: Resultsmentioning
confidence: 94%
“…In natural streams, statistical approaches were used in the past (e.g., refs and ). Earlier studies mostly focused on virus removal in constructed wetlands and waste stabilization ponds . In a study conducted on the Areuse River in Switzerland , bacteriophage H40/1 was used with the chemical tracer uranine.…”
Section: Introductionmentioning
confidence: 99%